GLOBAL SUPPLY CHAIN COMPLIANCE: DUE DILIGENCE, INTEGRITY CHALLENGES, AND ALIGNMENT WITH FCPA AND ESG STANDARDS - de Araújo, Daniela Cristina Abreu Jové (Revista Sistemática, 2021)
Global supply chains are increasingly exposed to legal, ethical, and reputational risks that arise from complex networks of suppliers operating across jurisdictions with varying levels of regulatory enforcement. Effective compliance programs require systematic due diligence on international suppliers to mitigate risks of corruption, fraud, and human rights violations. Companies face particular integrity challenges when operating in countries with high corruption risk, where weak enforcement and cultural variations complicate transparency. Aligning compliance efforts with international frameworks such as the U.S. Foreign Corrupt Practices Act (FCPA) and Environmental, Social, and Governance (ESG) standards strengthens organizational resilience, promotes ethical sourcing, and enhances investor and stakeholder trust. This paper analyzes the role of due diligence mechanisms, examines the ethical dilemmas of operating in high-risk markets, and evaluates the intersection of anti-corruption and sustainability frameworks in shaping modern supply chain governance.